Asymmetric Electrolytes Design for Aqueous Multivalent Metal Ion Batteries - Yang, Xiaochen; Wang, Xinyu; Xiang, Yue; Ma, Longtao; Huang, Wei (Nano-Micro Letters, 2023)
With the rapid development of portable electronics and electric road vehicles, high-energy-density batteries have been becoming front-burner issues. Traditionally, homogeneous electrolyte cannot simultaneously meet diametrically opposed demands of high-potential cathode and low-potential anode, which are essential for high-voltage batteries. Meanwhile, homogeneous electrolyte is difficult to achieve bi- or multi-functions to meet different requirements of electrodes. In comparison, the asymmetric electrolyte with bi- or multi-layer disparate components can satisfy distinct requirements by playing different roles of each electrolyte layer and meanwhile compensates weakness of individual electrolyte. Consequently, the asymmetric electrolyte can not only suppress by-product sedimentation and continuous electrolyte decomposition at the anode while preserving active substances at the cathode for high-voltage batteries with long cyclic lifespan. In this review, we comprehensively divide asymmetric electrolytes into three categories: decoupled liquid-state electrolytes, bi-phase solid/liquid electrolytes and decoupled asymmetric solid-state electrolytes. The design principles, reaction mechanism and mutual compatibility are also studied, respectively. Finally, we provide a comprehensive vision for the simplification of structure to reduce costs and increase device energy density, and the optimization of solvation structure at anolyte/catholyte interface to realize fast ion transport kinetics. Highlights: 1 The working principle of the asymmetric electrolyte and the long-term-seated contradictory issues were analyzed. 2 The characterization methods for the interfaces of anolyte/catholyte and electrolyte/electrode were summarized for revealing the fundamental mechanism of asymmetric electrolytes. 3 The future research directions for asymmetric electrolyte systems were proposed.